Modulation of multidrug resistance-associated proteins function in erythrocytes in glycerol-induced acute renal failure rats. (18th November 2016) - Matsushima, Aoi; Oda, Keisuke; Mori, Nobuhiro; Murakami, Teruo
Abstract: Objectives: Evaluation of the function of multidrug resistance-associated proteins (MRPs) expressed in erythrocytes and screening of endogenous MRPs modulator(s) in glycerol-induced acute renal failure (ARF) rats. Methods: Concentrations of 2, 4-dinitrophenyl-S-glutathione (DNP-SG), a substrate for MRPs, in erythrocytes after administration of 1-chloro-2, 4-dintrobenzene (CDNB), a precursor of DNP-SG, were determined in control and ARF rats. The screening of endogenous MRPs modulator(s) was performed using washed erythrocytes and inside-out erythrocyte membrane vesicles (IOVs) in vitro . Key findings: Accumulation of DNP-SG in erythrocytes was observed in ARF rats. Uraemic plasma components exhibited a greater inhibitory effect on DNP-SG uptake by IOVs than control plasma components and increased the DNP-SG accumulation significantly in washed erythrocytes. Several protein-bound uraemic toxins at clinically observed concentrations and bilirubin significantly inhibited DNP-SG uptake by IOVs. In washed erythrocytes, bilirubin (10 μm ) and l -kynurenine (100 μm ), a precursor of kynurenic acid being MRPs inhibitor, increased DNP-SG accumulation significantly. Conclusions: Glycerol-induced ARF rats contain various MRPs inhibitors in plasma, and membrane-permeable MRP substrates/inhibitors including their precursors inhibit the MRPs function in erythrocytes cooperatively.